A novel covalently grafted binder through in-situ polymerization for high-performance Si-based lithium-ion batteries. (20th December 2021) - Wang, Wei; Li, Yuchen; Wang, Yan; Huang, Weibo; Lv, Linze; Zhu, Guobin; Qu, Qunting; Liang, Yirui; Zheng, Wei; Zheng, Honghe
Highlights: A novel PVA-UFR binder is developed for Si-based lithium-ion batteries. The PVA-UFR binder can effectively suppress the volume effect of Si. The PVA-UFR binder constructs a unique Li-ion conducting network for Si anodes. A high quality SEI film is formed by using the PVA-UFR binder. The electrochemical performance of Si-based full cells is significantly improved. Abstract: Binder modification is an effective method to restrain the volume effect of Si anodes in high energy density lithium-ion batteries. In this work, a novel binder grafting strategy is proposed to prepare urea formaldehyde resin (UFR) grafted polyvinyl alcohol (PVA) binder to overall enhance the electrochemical performance of Si anodes. The advanced binder solves the problems of poor dispersibility, mechanical stability, and chemical stability of PVA binder. Benefit from the lithium conductivity and flexibility of the UFR modified PVA binder, the Si anode delivers over 2000 mAh/g after 200 cycles at a current density of 2.1 A/g, and retains 1837 mAh/g at 42 A/g. Furthermore, the PVA-UFR binder also exhibits obvious advantages in full cells, and the cycle stability of Si//LiFePO4 is significantly improved. Graphical abstract: Urea-formaldehyde resin grafted polyvinyl alcohol is developed as the binder of Si-based anodes, and the electrochemical performance of Si-based half cells and full cells is significantly improved. Image, graphical abstract